Consumer perceptions of the transition from coal to renewable energy in South Africa: Consumer perception toward the transition from fossil fuel to renewable energy technology for electricity generation in South Africa - Sebothoma, Captain (University of the Witwatersrand, Johannesburg, 2023)
The South African government has announced investments in renewable energy technology initiatives to address the electricity supply gap created by loadshedding and inefficiencies at Eskom, the country's power utility. However, a few studies on public acceptance on renewable energy technology have been undertaken in many countries, including one conducted in Nigeria by Rosemary Nike Wojuola, which found that the public always has some opposing thoughts on the deployment of such technologies. The purpose of the study was to understand the consumer's perceptions on the transition from fossil fuel to renewable energy technology for electricity generation in South Africa, and it will assist to improve policies that encourage consumers to embrace and learn about electricity generated by renewable energy sources. The “technology acceptance model’ and ‘theory of reasoned action” are used to evaluate the beliefs, attitudes, and perceptions concerning renewable energy technology in relation to sustainable behaviour. A quantitative approach (survey) was employed in this study to investigate South African electricity consumers' awareness of sustainable development (including knowledge, beliefs, perceptions, and attitudes). Statistical software (IBM SPSS Statistics version 28) was used to conduct inferential and descriptive statistical analysis on the collected data, allowing the researcher to derive predictions (or "inferences") from the data. The majority of participants, according to the data, had high levels of education (at least a graduate degree), which means that the sample does not represent the South African population as a whole. Based on the study findings, participant’s generally have an average level of knowledge regarding renewable energy technology, with females scoring lower than males. The results of a regression study between attitude calculated and behavioural intention of the consumers to adopt renewable energy technology were F=15.378 and p=0.001. This means that the research model fit the data and there was a positive association between the two variables (attitude calculated and behavioural intention). Lack of information, affordability, and unknown benefits of renewable energy technologies were the main barriers to participants' willingness to install renewables in their homes. Additionally, the study revealed that consumers depend on the government to speed up the development of renewable vi energy technologies for the production of electricity; however, there is evidence that the current administration is failing to maintain the existing fossil fuel infrastructure to ensure that the public has access to reliable electricity. The findings also show that the consumer's perception or attitude toward renewable energy technology is influenced by the perceived usefulness and ease of use, as well as the participants knowledge and beliefs about the technology. Thus, there is a need for renewable energy technology education that is sufficient to foster a favourable impression of renewable energy technologies among the general public. To foster a sustainable culture driven by the adoption of renewable energy technology for electricity generation across the country, sustainability should also be covered in education programs at all educational levels
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2023
Keywords: Consumer; Perception; Sustainable development; Renewable energy technology; Awareness; Behavioural intention; Knowledge; Belief; UCTD; Attitude; SDG-8: Decent work and economic growth